Sub-chronic low-dose arsenic in rice exposure induces gut microbiome perturbations in mice - Fubin Chen (Elsevier, 2021)
Long-term consumption of arsenic-contaminated rice has become a public health issue that urgently needs to be addressed. In this study, mice were exposed to arsenic in rice (low dose, 0.91 mg/kg; medium dose, 9.1 mg/kg) for 30 days and 60 days, respectively, and the effects on pathological structures of spleen and skin, as well as the structure of the fecal microbiome were examined. The findings revealed dose/time cumulative effects on pathological changes, with even a low dose exposure for 30 days causing destruction of splenic follicular structure and thickening of dermal keratinized and epidermal layers. The Firmicutes/Bacteroidetes ratio in the community and the positive/negative ratio in network links were higher in arsenic groups, suggesting that arsenic resulted in a less healthy and unstable microbiome for the host. Thus lifetime consumption of arsenic in rice may have potential health effects on humans and must be carefully assessed to safeguard human health. Furthermore, in arsenic groups, arsenic-resistant bacteria or arsenic hazards remediation bacteria changed to be the dominant bacteria and acted as the core bacteria in the network modules. Some microbial arsenic transforming genes (arsC, arsR, arsA, ACR3, and aoxB) differed, indicating that the gut microbiome changed to withstand arsenic stress. Furthermore, Faecalibaculum, Lachnospiraceae_NK4A136_group, Angelakisella, Ruminiclostridium, and Desulfovibrionaceae are positively associated with arsenic dosage and may be useful in the early detection of arsenicals.